Dark fermentation of complex waste biomass for biohydrogen production by pretreated thermophilic anaerobic digestate. (1st April 2015) - Ghimire, Anish; Frunzo, Luigi; Pontoni, Ludovico; d'Antonio, Giuseppe; Lens, Piet N.L.; Esposito, Giovanni; Pirozzi, Francesco
Abstract: The Biohydrogen Potential (BHP) of six different types of waste biomass typical for the Campania Region (Italy) was investigated. Anaerobic sludge pre-treated with the specific methanogenic inhibitor sodium 2-bromoethanesulfonic acid (BESA) was used as seed inoculum. The BESA pre-treatment yielded the highest BHP in BHP tests carried out with pre-treated anaerobic sludge using potato and pumpkin waste as the substrates, in comparison with aeration or heat shock pre-treatment. The BHP tests carried out with different complex waste biomass showed average BHP values in a decreasing order from potato and pumpkin wastes (171.1 ± 7.3 ml H2 /g VS) to buffalo manure (135.6 ± 4.1 ml H2 /g VS), dried blood (slaughter house waste, 87.6 ± 4.1 ml H2 /g VS), fennel waste (58.1 ± 29.8 ml H2 /g VS), olive pomace (54.9 ± 5.4 ml H2 /g VS) and olive mill wastewater (46.0 ± 15.6 ml H2 /g VS). The digestate was analyzed for major soluble metabolites to elucidate the different biochemical pathways in the BHP tests. These showed the H2 was produced via mixed type fermentation pathways. Highlights: The BHP of agro-industrial waste biomass from Campania Region (Italy) is evaluated. Agro-industrial wastes are promising substrates for DF biohydrogenation. BESA effectively prepares the hydrogen producing seed inoculum. Fermentation pathways are helpful to optimize the BHP performance.